Las palabras compuestas en el aimara de Conima - Lovón Cueva, Marco Antonio (2019)
Within the processes of word formation, the morphological mechanism of the compounding has been little studied in Aymara and other Andean languages. This survey shows a description of the ways in which the compound words are formed in the grammar of Conima Aymara. Therefore, this work analyzes the structure and the syntactic combination of the composition in this linguistic variety. The data has been collected from the speakers and from the main dictionaries in Aymara. The present investigation concludes that the Conima Aymara forms compounds from six syntactic patterns that follow the complement-core structure. Finally, in relation to its typology, this survey points out that the Conima Aymara basically creates nominal compounding.